The Qualification of Jarimah Ta’zir for Child Exploitation: A Case Study of Forced Labor at the Muara Parlampungan Gold Mine - Lubis, Sri Anggini; Mukhsin, Abd. (CV. Social Politic Genius (SIGn), 2025)
This research examines the phenomenon of child exploitation in the informal gold mining sector of Muara Parlampungan Village. This practice is opposed to the principles of child protection in Islam. Amid the ideal narrative of children as a divine trust whose dignity must be preserved, the on-the-ground reality reveals the systematic coercion of school-aged children, who are forced to work in high-risk conditions to support their families’ economy. The purpose of this study is to analyze this practice from the perspective of Islamic criminal law (fiqh jinayah) and to formulate a religio-legal (syar’i) qualification for the act. Using a juridical-empirical approach and a qualitative method, primary data were collected through observation and in-depth interviews with child victims, religious figures, and community leaders. The results reveal that children are forced to work 12-hour days in a hazardous environment. These conditions constantly threaten their physical and psychological safety, resulting in the deprivation of their fundamental right to education and inducing deep trauma with the potential for lifelong effects. An analysis based on the higher objectives of Islamic law (Maqashid al-Syariah) proves that this act directly undermines three fundamental objectives: the preservation of life (hifz al-nafs), the intellect (hifz al-‘aql), and progeny (hifz al-nasl). Based on this systematic harm, the study concludes that this practice of child coercion qualifies as a criminal offense (jarimah) falling under the category of a discretionary punishment (ta’zir). This qualification provides the state with full legitimacy to undertake legal intervention. The research recommends a hybrid law enforcement model that combines rehabilitative sanctions for parents with comprehensive restorative programs for child victims to break the cycle of exploitation.